Dengue’s climate conundrum: how vegetation and temperature shape mosquito populations and disease outbreaks - Mohd Hardy Abdullah, Nur Athen; Che Dom, Nazri; Salleh, Siti Aekball; Dapari, Rahmat; Precha, Nopadol (BioMed Central Ltd, 2025)
Introduction: Dengue, a prevalent mosquito-borne viral disease in tropical regions, is influenced by environmental factors such as rainfall, temperature, and urbanization. This study aims to assess the effects of microclimate, vegetation, and Aedes species distribution on dengue transmission in distinct hotspot and non-hotspot locations. Methods: This cohort study was conducted in two sites within Selangor, Malaysia: a recurrent dengue hotspot and a non-dengue hotspot. Microclimatic variables (temperature, humidity, and rainfall) were monitored over six months using data loggers, and vegetation cover was assessed through visual estimation and GIS mapping. Adult Aedes mosquitoes were collected using Gravid Oviposition Sticky (GOS) traps and identified to species level. Dengue virus presence was detected using ProDetect® Dengue NS1 Ag Rapid Test. Weekly indices for mosquito abundance and dengue risk were calculated, and statistical analyses were performed to explore correlations between microclimate, vegetation, and mosquito indices. Results: In the non-dengue hotspot, Aedesalbopictus was the predominant species, while both Aedesaegypti and Ae.albopictus coexisted in the dengue hotspot. No dengue virus was detected in Ae.albopictus, while intermittent virus presence was noted in Ae.aegypti within the dengue hotspot. Significant microclimatic differences were observed: non-dengue hotspot had higher mean humidity and lower minimum temperatures, influenced by greater vegetation cover. In contrast, dengue hotspot showed lower humidity and higher minimum temperatures. Correlation analyses indicated positive associations between temperature and mosquito abundance, with variations in vegetation cover impacting local microclimatic conditions. Conclusion: This study demonstrates how vegetation and microclimatic conditions shape Aedes mosquito distribution and dengue risk. Findings highlight the need for targeted urban planning and community interventions that reduce mosquito breeding habitats, with special attention to vegetation management and environmental modifications to control dengue transmission.